2022
DOI: 10.1101/2022.02.26.22271509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of booster vaccination against Delta and Omicron variants in Iceland

Abstract: By the end of July 2021, the majority of the Icelandic population had received vaccination against COVID-19. In mid-July a wave of SARS-CoV-2 infections, dominated by the delta variant, spread through the population, followed by an omicron wave in December. A booster vaccination campaign was initiated to curb the spread of the virus. We estimated the risk of infection for different vaccine combinations using vaccination data from 276,028 persons and 963,557 qPCR tests for 277,687 persons. We measured anti-Spik… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that protection conferred by booster vaccination wanes ( 54 56 ). Currently, the data necessary to use this approach to evaluate the durability of immunity following booster vaccination are not available to expand our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that protection conferred by booster vaccination wanes ( 54 56 ). Currently, the data necessary to use this approach to evaluate the durability of immunity following booster vaccination are not available to expand our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, Iceland saw a small second wave in August 2020, and a larger third wave of infections in late September through to early November 2020 [ 29 31 ]. A fourth wave of COVID-19 cases then hit Iceland in mid-July 2021 dominated by Delta variant infections [ 32 ]. New restrictions were then introduced in November and December 2021 in response to the fifth wave caused by the rapidly spreading Omicron variant [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A fourth wave of COVID-19 cases then hit Iceland in mid-July 2021 dominated by Delta variant infections [ 32 ]. New restrictions were then introduced in November and December 2021 in response to the fifth wave caused by the rapidly spreading Omicron variant [ 32 ].…”
Section: Resultsmentioning
confidence: 99%